Biochemical responses and DNA damage induced by herbicide QYR301 in earthworm (Eisenia fetida). (April 2020) - Wang, Hengzhi; Zhang, Xiaolin; Wang, Lipeng; Zhu, Baolin; Guo, Wenlei; Liu, Weitang; Wang, Jinxin
Abstract: QYR301, a novel herbicidal inhibitor of 4-hydroxyphenylpyruvate dioxygenase (HPPD), has great potential for resistant weed control in paddy fields, but massive use of pesticides may result in toxicity to soil non-target organisms. Thus, this study was designed to assess subchronic toxicity of different doses of QYR301 in artificial soil (0, 0.1, 1.0, 2.5, and 5.0 mg kg −1 ) to earthworms ( Eisenia fetida ) on days 7, 14, 21, and 28 after exposure, using biomarkers of reactive oxygen species (ROS) and malondialdehyde (MDA) contents, activities of catalase (CAT), superoxide dismutase (SOD), peroxidase (POD) and glutathione-S-transferase (GST), and DNA damage. The ROS content significantly increased for all treatments on 7 and 14 days then decreased, and recovered to control level for 0.1 and 1.0 mg kg −1 treatment on day 28. Concerning enzymes activities, QYR301 increased POD, SOD, and GST activities, but inhibited CAT activity. Except for POD activity, SOD, CAT, and GST activities of 0.1 mg kg −1 group recovered to control level on day 28. Also, the MDA content of 0.1 mg kg −1 group reached control level on day 28. However, DNA damage was observed for all treatments throughout the experiment and it increased with increasing doses and time except for 5.0 mg kg −1 treatment on day 28. These results suggested that QYR301 induced excessive ROS production leading to oxidative stress in earthworms, which caused lipid membrane peroxidation and DNA damage ultimately. The findings could provide a theoretical foundation for assessing ecological damage of QYR301 to soils and a guide for future QYR301 applications. Graphical abstract: Image 1 Highlights: The subchronic toxicity of QYR301 herbicide to earthworms was initially investigated. QYR301 induced ROS production, lipid peroxidation and DNA damage in earthworms. Earthworms themselves exposed to 0.1 and 1.0 mg kg −1 reduced oxidative stress. The ROS, MDA content and SCGE were more sensitive biomarkers in the present study.